(untitled) (Tempo e Argumento, 2022)
This study aims to discuss a new approach to global history: the rhizome perspective. Based on the epistemological model of Gilles Deleuze and Félix Guattari, a new paradigm will be advocated, explaining what is new and original in a global history thus envisaged, considering the virtues and limits that this approach entails. In the last quarter of a century, all over the world, very decisive transformations have taken place at the socioeconomic, cultural and political level. This atmosphere of change, many of which undeniable advances for the well-being of contemporary society, such as automation, the technological revolution, and the exponential and irreversible growth of the virtual world, has launched new challenges that some social and human sciences have not yet managed to give a satisfatory answer. In this context of superfluity, the conventional instruments of research, reflection and analysis in the context of history, or rather, the production of historical knowledge, have been refined and in some cases replaced. With its focus on integration and connection, global history emerged from this context, proving to be a convincing proposal for the construction of a historical knowledge that is both comprehensive and deep, showing however limits that force us to reflect on how this model, not yet dominant, can in Brazilian historiography, from a theoretical-methodological point of view, to be improved. That’s what this article proposes. Keywords: global history; rhizome; new paradigm.